2000
DOI: 10.1080/03601230009373253
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of pesticide residues in a cotton crop soil

Abstract: This paper reports on the residues of methyl parathion (O,O-dimethyl O-4-nitrophenyl phosphorothioate), trifluralin (alpha, alpha, alpha-trifluoro-2,6-dinitro-N,N-dipropyl-p-toluidine), endosulfan [(1, 4, 5, 6, 7, 7-hexachloro-8, 9, 10-trinorborn-5-en-2, 3-ylenebismethylene) sulfite] and dimethoate (O, O-dimethyl S-methylcarbamoylmethyl phosphorodithioate) in a cotton crop soil. Soil samples (0-15 cm) were collected at different periods from the cotton crop farm and subjected to Soxhlet extraction. The extract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 1 publication
0
10
0
1
Order By: Relevance
“…Six other steroids showed no cross-reactivity. Standards ranged from between 0.98 and 1,000 pg/tube, and all tubes were incubated in 5,000 cpm [2,4,6,7,16, H]estradiol (Amersham Life Science, Buckinghamshire, UK). Serial dilutions of extracted plasma showed parallelism with a standard curve.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Six other steroids showed no cross-reactivity. Standards ranged from between 0.98 and 1,000 pg/tube, and all tubes were incubated in 5,000 cpm [2,4,6,7,16, H]estradiol (Amersham Life Science, Buckinghamshire, UK). Serial dilutions of extracted plasma showed parallelism with a standard curve.…”
Section: Methodsmentioning
confidence: 99%
“…It is used on a wide variety of crops including tea, coffee, cotton, fruits, and vegetables, as well as on rice, cereals, maize, or other grains (5). Several studies reported the presence of endosulfan in cotton crop soils [0.1-0.4 mg/kg (6)] and estuaries [0. .0 µg/L (7)], and relatively high residual levels have been found in some marketed fruits such as Brazilian strawberries and tomatoes [4-510 ppb (8)].…”
Section: Endosulfan Exposure Disrupts Pheromonal Systems In the Red-smentioning
confidence: 99%
“…Residues in Sonsonate soil samples averaged 7.14 mg-kg" 1 , while in Ahuachapan, one sample contained as much as 16.47 mg-kg" 1 paraquat [15]. Tatui soils from Sao Paulo State, Brazil, contained trifluraline residues of 1.2 mg-kg" 1 six weeks after application also methyl parathion residues up to 2 mg-kg" 1 [16]. Reports on residues of newer pesticides in soil are rare.…”
Section: Pesticides Residues In Tropical Soilsmentioning
confidence: 99%
“…It is primarily used on a wide variety of crops including tea, coffee, cotton, fruits, and vegetables, as well as on rice, cereals, maize, or other grains. Several studies reported the presence of endosulfan in cotton crop soils (0.1-0.4 mg/kg; Luchini et al, 2000) and estuaries (0.5-4.0 ug/L; Fox and Matthiessen, 1982), and relative^ high residual levels have been found in some marketed fruits such as Brazilian strawberries and tomatoes (4-510 ppb endosulfan; Araujo et al, 1999). These reports indicate that endosulfan exposure can occur in both human and wildlife populations.…”
mentioning
confidence: 93%